Peningkatan Pemahaman Konsep Pecahan Melalui Media Cuisenaire Rods Dengan Pendekatan Concrete-Pictorial-Abstract Kelas III Sekolah Dasar - Kartika, Deswita; Sari, Pratiwi Kartika; Azzahra, Salsabilah (Universitas Muhammadiyah Magelang, 2025)
This study aims to improve the understanding of fraction concepts in grade III elementary school students through Cuisenaire Rods media with Concrete-Pictorial-Abstract (CPA) approach. The background is the low understanding of fractions due to conventional learning methods that only rely on memorizing formulas. This research is a Classroom Action Research (PTK) conducted at SD Negeri Pondok Benda 01, Pamulang, South Tangerang City, with 26 students as subjects. The research was conducted in two cycles using the Kemmis and McTaggart model. Data were collected through observation, tests, and documentation, which were analyzed descriptively qualitative and simple quantitative. The results showed a significant increase in students' understanding of fraction concepts: in the pre-cycle the percentage of completeness was only 46%, increased to 77% in cycle I, and reached 92% in cycle II. Cuisenaire Rods media and CPA approach effectively help students understand fractions gradually according to cognitive development. Thus, the media and approach significantly increased students' engagement, enthusiasm, and understanding of the concept of fractions. The improvement of students' learning outcomes can be seen from the increasing number of students who achieve learning completeness in fraction material after the implementation of the action. The research recommends the use of concrete media and the CPA approach as a strategy for learning mathematics in elementary schools.